Eroica - Gardiner, John Eliot 1943- (Opus Arte, 2004)
Period-drama depiction of the private, first performance of Beethoven's "Eroica" symphony at the Lobkowitz Palace in 1805, the momentous musical event that prompted composer Joseph Haydn to remark "Everything is different from today."